Conjunctival Leiomyosarcoma: A Report of Two Cases. (3rd September 2015) - Nair, Akshay G.; Kaliki, Swathi; Kamal, Saurabh; Mishra, Dilip K.; Vemuganti, Geeta K.
ABSTRACT: Purpose : Leiomyosarcoma is a common soft tissue tumor in the body. However, ocular leiomyosarcoma is rather uncommon. Herein, we describe the clinical and histopathological features of two cases of conjunctival leiomyosarcoma. There have only been three previously documented cases of conjunctival leiomyosarcoma. Results : A 34-year-old male presented with a 2-year history of a whitish mass in the right eye. He underwent an incisional biopsy of the mass, which supported the diagnosis of leiomyosarcoma on histopathological examination. Computed tomography showed orbital extension of the mass, following which he underwent an eyelid sparing orbital exenteration of the right side. The second case was that of a 39-year-old male, who had a history of a whitish limbal mass, which had been previously excised elsewhere. The pre-operative clinical photographs and histopathology slides of the excised mass were reviewed. A histopathological diagnosis of conjunctival leiomyosarcoma was established and due to base positivity, he was treated with plaque radiotherapy. Both the cases showed no tumor recurrence or systemic metastasis at one-year follow-up. Conclusion : Primary conjunctival leiomyosarcoma is uncommon. Appropriate treatment of the tumor is associated with good prognosis.